Baseline serum uric acid level is associated with progression-free survival, disease control rate, and safety in postoperative patients with colorectal cancer treated by FOLFOX, FOLFIRI, or XELOX - Zhang, Xi; Chen, Qing-hong; Yang, Ying; Lin, Jing-xin; Li, Yan-chun; Zhong, Tian-yu; Chen, Jie; Wu, Si-qi; Chen, Xiao-hu; Zhou, Rui-si; Lin, Jia-man; Wang, Dong-qing; et al. (Frontiers in Oncology, 2022)
Background High serum uric acid (SUA) levels increase the risk of overall cancer morbidity and mortality, particularly for digestive malignancies. Nevertheless, the correlation between SUA level and clinical outcomes of the postoperative patients with colorectal cancer (CRC) treated by chemotherapy is unclear. This study aimed at exploring the relationship between baseline SUA level and progression-free survival (PFS), disease control rate (DCR), and safety in postoperative CRC patients receiving chemotherapy. Patients and Methods We conducted a retrospective study to evaluate the relationship between baseline SUA level and PFS, DCR, and incidence of serious adverse events of 736 postoperative CRC patients treated with FOLFOX, FOLFIRI or XELOX at our center. Results Data from our center suggested that high baseline SUA level is linked to poor PFS in non-metastatic CRC patients using FOLFOX (HR=2.59, 95%CI: 1.29-11.31, p=0.018) and in male patients using FOLFIRI (HR=3.77, 95%CI: 1.57-39.49, p=0.012). In patients treated by FOLFIRI, a high SUA is also linked to a low DCR (p=0.035). In patients using FOLFOX, high baseline SUA level is also linked to a high incidence of neutropenia (p=0.0037). For patients using XELOX, there is no significant correlation between SUA level and PFS, effectiveness, or safety. Conclusions These findings imply that a high SUA level is a promising biomarker associated with poor PFS, DCR and safety of postoperative CRC patients when treated with FOLFOX or FOLFIRI.